The grayness of match-fixing: a study of the prevalence and sanctionability of non-betting-related match-fixing in football and tennis - Vanwersch, Lucie (Deviant behavior, 2025)
In this study, we provide a nuanced perspective on a sub-type of match-fixing, called non-betting-related match-fixing (NBMF). Using a cross-sectional survey, we measured the prevalence and motives behind NBMF in Belgian amateur football and tennis. Additionally, we conducted a thorough study of the regulatory documents of the relevant (sports) organizations to examine the sanctionability of different types of NBMF by analyzing their disciplinary regulations surrounding NBMF and, if applicable, their sanctioning guidelines. Furthermore, various instances of NBMF were applied to the definition of competition manipulation of the Council of Europe’s Macolin Convention. We conclude that NBMF is not always linked to sporting outcomes and that the gray zone that surrounds it differs between both sports depending on the specificity of their regulations, and the subjectivity with which they are implemented in practice.